HUBUNGAN ANTARA PERSEPSI PROMOSI DENGAN PERILAKU PEMBELIAN IMPULSIF - Yoga Dianraka; Brigitan Argasiam (IMAGE, 2024)
This research aims to determine the relationship between promotional perceptions and impulsive buying behavior. The sampling technique in this research was accidental sampling. Data collection in this research used an impulsive buying behavior scale and a promotion perception scale. The subjects were 35 students from the business economics faculty at Unika Soegijapranata. The research was conducted using quantitative methods. Based on the results of product moment correlation data analysis, the correlation coefficient value was obtained at rxy 0.482 with p<0.01. This shows that there is a very significant positive relationship between promotional perceptions and impulsive buying behavior. The higher the perceived promotion, the higher the impulse buying behavior and vice versa. In this way, the hypothesis proposed by the researcher is accepted. Keywords: promotion perception, impulse buying behavior.